Indigenising the study of Multicultural Understanding at the Sámi University College - Balto, Asta Mitkijá; Østmo, Liv (Sámi dieđalaš áigečála, 2026)
In this article, we examine our experiences of carrying out – and teaching for about ten years – a course called Multicultural Understanding (in Sami máŋggakultuvrralaš áddejupmi, MKÁ) in the Sámi University College. We focus on the way of working in the course in which the emphasis is on the position and the telling of stories. We also analyze how this method has contributed to the students learning process. Furthermore, we assess how this way of working influences the conditions of learning and look at how we can change and improve the education. The article shows that the enhancing of cultural sensitivity and an analytic way of thinking are central elements of the course on multicultural understanding. It also shows that this approach makes the experiences and feelings of the students themselves visible, because – compared with ordinary courses – the course gives them ‘more room’. This way of working entails that the students can express their experiences through stories. The stories have provided content for the course and connected it with relevant and topical discussions in society. Often, they have also served as a beginning for the papers that students have written in connection with more comprehensive project work. Narration plays, of course, a central role in Sami heritage and this article also examines whether, through the approach of the course and the provision of a learning opportunity, we have created a Sami learning environment, or “a shared room”, which contributes to human selfimprovement, analytical cultural understanding and good reflective skills in the students. While reflecting on this education, we realized that the course needs to have an even stronger indigenous perspective, which deals with power relations and the effect of colonisation but also focuses on recovery. The education could be reformed to include the learning process of decolonisation, for which indigenous researchers have developed methodologies. It may contain elements that could be used in our course on multicultural understanding, to promote the empowerment of the Sami and other indigenous peoples.